Kepemimpinan Pastoral Transformasional dan Resiliensi Jemaat di Era Digital: Tinjauan Literatur Integratif dalam Konteks Gereja Injili Indonesia - Wennar Wennar; Tedjo Tony; Daniel Ari Wibowo (KAPATA: Jurnal Teologi dan Pendidikan Kristen, 2026)
Digital transformation has reshaped patterns of communication, community formation, and church worship practices, while simultaneously creating opportunities for disinformation, fragmented attention, and weakened interpersonal relationships among congregants. Although studies on transformational leadership, digital literacy, and community resilience have developed independently, theological-pastoral syntheses that systematically integrate these three domains remain limited, particularly within the context of Evangelical churches in Indonesia. This study aims to formulate a conceptual framework of transformational pastoral leadership that can strengthen congregational resilience amid digital disruption. Employing an integrative literature review approach, the study examines relevant sources and synthesizes interdisciplinary findings through thematic analysis. The findings indicate that congregational resilience is fostered through three principal domains. First, apologetic-doctrinal teaching strengthens congregants’ critical capacity to respond to misinformation and doctrinal distortion. Second, contextual digital literacy equips congregants to evaluate, verify, and manage online information responsibly. Third, adaptive spiritual formation sustains relationships, participation, and intergenerational solidarity within digital environments. Based on this synthesis, the study proposes an integrative pastoral framework that positions pastors not only as teachers and guardians of doctrine but also as architects of a healthy digital ecosystem that nurtures spiritual growth and communal resilience. This study contributes to the development of digital pastoral theology and provides a conceptual foundation for local church ministry in the era of digital transformation.